Lexicon for guidance terminology in pediatric hematology/oncology: A White Paper. Issue 4 (23rd January 2020) - Dupuis, L. Lee; Robinson, Paula D.; van de Wetering, Marianne D.; Tissing, Wim; Seelisch, Jennifer; Digout, Carol; Sung, Lillian; Phillips, Robert; ,
Abstract: Terms used to label types of clinical recommendations and guidance are applied inconsistently and do not reflect the methods used to create each type. Here, the international Pediatric Oncology Supportive Care Guideline Network proposes a lexicon for types of recommendations and guidance documents. A lexicon describing three types of recommendations (clinical practice guideline–derived, good practice statement, and expert opinion statement) and two types of guidance documents (clinical practice guideline and expert opinion) is presented. Consistent use of this lexicon will allow pediatric oncology clinicians to readily appreciate the methods used to create clinical guidance.